1970
DOI: 10.1177/00220345700490030901
|View full text |Cite
|
Sign up to set email alerts
|

Combined Effect of Trace Elements and Fluorine on Caries

Abstract: Caries examinations of 251 children aged 12 to 14, from two Ohio towns that use water supplies with high contents of boron and strontium showed a mean DMFS score of 3.56 compared to a score of 5.54 in a control group of 338 children. Findings suggest that the significantly lower caries prevalence in the former group is related to the boron and strontium content of the water rather than a 0.2 ppm difference in the fluorine level.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
30
1

Year Published

1972
1972
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(32 citation statements)
references
References 3 publications
1
30
1
Order By: Relevance
“…Even with no contribution from fall-out, Sr is a constant trace element in teeth, though wide variations are found in the enamel of different teeth and the range varies from 25 to 600 p.p.m, in teeth from different geographic areas (Steadman, Brudevold & Smith, 1958). Caries examinations conducted in three Ohio communities, two of which 0567-7408/80/071525-06501.00 had high levels of Sr and B in their drinking water and soil product (5.30 and 5.45 p.p.m, of Sr and 0.31 and 0.39 p.p.m, of B in water) and one of which contained low levels (0.20 p.p.m, of Sr and 0.04 p.p.m, of B in water), showed lower caries activity in the communities where drinking water contained a higher level of Sr and B (Curzon, Adkins, Bibby & Losee, 1970). Little & Barrett (1976a,b), from their studies of caries prevalence in the Atlantic Coast and West Coast areas of the USA, found that both F and Sr were incorporated in enamel at a statistically predictable level in the teeth of persons with little caries and that the enamels of people with low caries incidence had similar Sr compositions (300-400 p.p.m.…”
Section: Introductionmentioning
confidence: 97%
“…Even with no contribution from fall-out, Sr is a constant trace element in teeth, though wide variations are found in the enamel of different teeth and the range varies from 25 to 600 p.p.m, in teeth from different geographic areas (Steadman, Brudevold & Smith, 1958). Caries examinations conducted in three Ohio communities, two of which 0567-7408/80/071525-06501.00 had high levels of Sr and B in their drinking water and soil product (5.30 and 5.45 p.p.m, of Sr and 0.31 and 0.39 p.p.m, of B in water) and one of which contained low levels (0.20 p.p.m, of Sr and 0.04 p.p.m, of B in water), showed lower caries activity in the communities where drinking water contained a higher level of Sr and B (Curzon, Adkins, Bibby & Losee, 1970). Little & Barrett (1976a,b), from their studies of caries prevalence in the Atlantic Coast and West Coast areas of the USA, found that both F and Sr were incorporated in enamel at a statistically predictable level in the teeth of persons with little caries and that the enamels of people with low caries incidence had similar Sr compositions (300-400 p.p.m.…”
Section: Introductionmentioning
confidence: 97%
“…As early as 1953, the importance of strontium in low caries prevalence was suggested [4]. Since then, several reports emphasized the effect that strontium has on dental caries levels [5][6][7]. The levels of strontium in enamel of premolars from patients with low DMF (Decayed, Missing, and Filled teeth) were significantly higher than the levels found in patients with high DMF [7].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, Sr is known to substitute for Ca in these tissues. Strontium has also been suggested as a caries inhibitor (Curzon, Adkins, Bibby & Losee, 1970). The fact that octastrontium phosphate does not form under conditions suitable for the formation of octacalcium phosphate (Schnell, Kiesewetter, Kim & Hayek, 1971) shows a difference between strontium phosphates and calcium phosphates in crystallization properties.…”
mentioning
confidence: 99%